Hematological and blood metabolite response in relation to the conception rate of Pasundan cows with synchronized estrous and ovulation - Setiawati, E. N.; Sumaryadi, M. Y.; Saleh, D. M. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
Twenty pasundan cows were divided into two treatments int his study aims to determine the correlation between hematological and blood metabolite on the conception rate of Pasundan cows with synchronized estrus and ovulation. Twenty pasundan cows were divided into two treatments 1) estrus synchronization through double injection 5 ml PGF2α , 2)combination of 5 ml PGF2α per cow and 2.5 ml GnRH per cow intramuscularly. The heat of cow is immediately inseminated 2 times with an interval of 6 hours. The observed variables were estrus percentage, conception rate, erythrocyte, leucocyte, hemoglobin, β-hydroxy butyric acid (BHBA), blood urea nitrogen (BUN), and non esterificated acid (NEFA). Data were processed by analysis of variance and correlation- regression. The result showed that PGF2α with GnRH injection resulted in a better conception rate than that of PGF2α (70% vs 60%), the average plasma concentration of erythrocyte, leucocyte, hemoglobin, NEFA, BUN, and BHBA levels respectively was 6.61±0.19 million/µl, 11.30±0.35 thousand/µl, 10.63±0.35 g/dL, 1.65±018 mmol/L, 10.28±1.50 mg/dL, 21.46±1.96 mg/dL. The data obtained were performed variance analysis and correlation regression analysis using SPSS 16.0. The results of the regression analysis showed that the concentration of erythrocytes, leucocytes, hemoglobin, NEFA, BUN, and BHBA had a significant relationship (P<0.05) with pregnancy, and coefficient of determination were 86.4%, 69.1%, 98.3%, -11.7%, -8.2%, -7.0%, respectively. It was concluded that the pregnancy of Pasundan cows has a strong relation between the conception rates with hematological, however blood metabolites showed a weak relation and inversely proportional.